If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4h = 5h + -60 Reorder the terms: 4h = -60 + 5h Solving 4h = -60 + 5h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-5h' to each side of the equation. 4h + -5h = -60 + 5h + -5h Combine like terms: 4h + -5h = -1h -1h = -60 + 5h + -5h Combine like terms: 5h + -5h = 0 -1h = -60 + 0 -1h = -60 Divide each side by '-1'. h = 60 Simplifying h = 60
| 3x+18=4x+13 | | y=(2t(5-t)) | | 150m-100m+42750=45450-175m | | 3m+167=4m+55 | | 21=6+x+-4x | | 2.3p=46 | | 5x-7=3x+27 | | 0.7x-2.1=1.5x+2.7 | | -3(8x+10)=6(-4x-14) | | 5(v+7)+7v=23 | | 5j+33=18 | | (-3)(2x-5)-8=7-x | | 20-0.5x=21 | | 4b-6-12b-5= | | (x-3)(x-3)=36 | | 4(u-6)+3u=32 | | 6(7a-1)=8(4a+11) | | 14=7x+4-2x | | 7x-(5x+13)= | | 3f+10f=26 | | x^2+64-225=0 | | a-8s=8(9-st) | | y=-0.6x+4 | | -8y+2(y+6)=18 | | 30=6a+12 | | 0=(2x^2)-16 | | 29-7x=17+5x | | x+35=-7x-35 | | -3.3=x+(-1.1) | | -6z-4=-10 | | 40c-.05(40c)=190 | | -4.9x^2+100x=0 |